Component analysis of the fast photoelectric signal from model bacteriorhodopsin membranes: Part II. Effect of fluorescamine treatment - Okajima, Ting L.; Michaile, Sherie; McCoy, Lowell E.; Hong, Felix T. (Bioelectrochemistry and Bioenergetics, 1994)
This report investigates the effect of fluorescamine treatment of bacteriorhodopsin on the fast photoelectric signal. Such a treatment was performed either before or after membrane reconstitution. The data so obtained are subject to component analysis as outlined in the first of the two companion papers. The analysis shows that the fluorescamine treatment inhibits the B2 component but leaves the B1 component intact. The result justifies our protocol of separating the signal into the B1 and the B2 components. The result is also consistent with the assignment of B1 to a molecular process located in the buried chromophore-binding region and the assignment of B2 to an interfacial proton binding process taking place at the cytoplasmic surface of the membrane.